Monastic Education and Moral Development: A Study of Novice Monks at Wat Prey Speu, Cambodia - Prak Polla; Phal Sophoeun (SUJANA: Education and Learning Review, 2026)
The quality of teaching and learning within religious educational institutions remains an underexplored dimension of educational research, particularly in the context of Buddhist monastic primary schooling in Southeast Asia. This study investigates the effectiveness of Buddhist education at Wat Prey Speu Buddhist Primary School in Phnom Penh, Cambodia, with particular emphasis on its role in fostering moral development, implementing transformational educational models, and advancing the influence of spiritual advisors on novice monks' holistic formation. A sequential explanatory mixed-methods design was employed, integrating quantitative survey data collected from 141 participants, selected through the Slovin formula from a total population of 220, with qualitative data derived from semi-structured interviews, student focus groups, and classroom observations. Multiple regression analysis identified the school environment as the strongest predictor of moral development (R² = .822), followed by teachers' dual roles (R² = .451) and curricular integration of Buddhist principles (R² = .115). Qualitative findings further confirmed that the monastic environment functions as an immersive pedagogical space in which Buddhist values are actively practiced rather than passively received. The study concludes that Wat Prey Speu represents a replicable model of values-based holistic education and recommends that the Cambodian Ministry of Education consider integrating its foundational principles into the national educational framework.